Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Sure, let's break down the solution step-by-step for each part of the problem.
### Part A: Factoring the equations
1. Equation: [tex]\( x^2 - 36 \)[/tex]
This is a difference of squares. The formula for the difference of squares is [tex]\( a^2 - b^2 = (a - b)(a + b) \)[/tex]. Here, [tex]\( a = x \)[/tex] and [tex]\( b = 6 \)[/tex], so:
[tex]\[ x^2 - 36 = (x - 6)(x + 6) \][/tex]
2. Equation: [tex]\( 9x^2 - 1 \)[/tex]
This is also a difference of squares where [tex]\( a = 3x \)[/tex] and [tex]\( b = 1 \)[/tex]. Applying the formula:
[tex]\[ 9x^2 - 1 = (3x - 1)(3x + 1) \][/tex]
3. Equation: [tex]\( 4x^2 - 16 \)[/tex]
First, notice that 4 is a common factor in both terms:
[tex]\[ 4x^2 - 16 = 4(x^2 - 4) \][/tex]
Then [tex]\( x^2 - 4 \)[/tex] is a difference of squares where [tex]\( a = x \)[/tex] and [tex]\( b = 2 \)[/tex]:
[tex]\[ x^2 - 4 = (x - 2)(x + 2) \][/tex]
Therefore:
[tex]\[ 4x^2 - 16 = 4(x - 2)(x + 2) \][/tex]
Thus, the factored forms of the equations are:
- [tex]\( x^2 - 36 \)[/tex] factors into [tex]\( (x-6)(x+6) \)[/tex].
- [tex]\( 9x^2 - 1 \)[/tex] factors into [tex]\( (3x-1)(3x+1) \)[/tex].
- [tex]\( 4x^2 - 16 \)[/tex] factors into [tex]\( 4(x-2)(x+2) \)[/tex].
### Part B: Non-equivalent Factored Forms
All the provided equations were factorable using the difference of squares method. There are no binomials in part A that did not have an equivalent factored form.
### Part C: Products using Properties of Complex Numbers
The products can be derived by simply expanding the factored forms back:
1. Product of [tex]\( (x - 6)(x + 6) \)[/tex]:
[tex]\[ (x - 6)(x + 6) = x^2 - 36 \][/tex]
2. Product of [tex]\( (3x - 1)(3x + 1) \)[/tex]:
[tex]\[ (3x - 1)(3x + 1) = 9x^2 - 1 \][/tex]
3. Product of [tex]\( 4(x - 2)(x + 2) \)[/tex]:
[tex]\[ 4(x - 2)(x + 2) = 4(x^2 - 4) = 4x^2 - 16 \][/tex]
Thus, the products of each expression, reaffirming the given factored forms, are the original expressions:
- [tex]\( (x-6)(x+6) = x^2 - 36 \)[/tex]
- [tex]\( (3x-1)(3x+1) = 9x^2 - 1 \)[/tex]
- [tex]\( 4(x-2)(x+2) = 4x^2 - 16 \)[/tex]
These steps confirm the accuracy and correctness of the original information, ensuring that the factored forms are appropriate and that all of the provided binomials are factorable.
### Part A: Factoring the equations
1. Equation: [tex]\( x^2 - 36 \)[/tex]
This is a difference of squares. The formula for the difference of squares is [tex]\( a^2 - b^2 = (a - b)(a + b) \)[/tex]. Here, [tex]\( a = x \)[/tex] and [tex]\( b = 6 \)[/tex], so:
[tex]\[ x^2 - 36 = (x - 6)(x + 6) \][/tex]
2. Equation: [tex]\( 9x^2 - 1 \)[/tex]
This is also a difference of squares where [tex]\( a = 3x \)[/tex] and [tex]\( b = 1 \)[/tex]. Applying the formula:
[tex]\[ 9x^2 - 1 = (3x - 1)(3x + 1) \][/tex]
3. Equation: [tex]\( 4x^2 - 16 \)[/tex]
First, notice that 4 is a common factor in both terms:
[tex]\[ 4x^2 - 16 = 4(x^2 - 4) \][/tex]
Then [tex]\( x^2 - 4 \)[/tex] is a difference of squares where [tex]\( a = x \)[/tex] and [tex]\( b = 2 \)[/tex]:
[tex]\[ x^2 - 4 = (x - 2)(x + 2) \][/tex]
Therefore:
[tex]\[ 4x^2 - 16 = 4(x - 2)(x + 2) \][/tex]
Thus, the factored forms of the equations are:
- [tex]\( x^2 - 36 \)[/tex] factors into [tex]\( (x-6)(x+6) \)[/tex].
- [tex]\( 9x^2 - 1 \)[/tex] factors into [tex]\( (3x-1)(3x+1) \)[/tex].
- [tex]\( 4x^2 - 16 \)[/tex] factors into [tex]\( 4(x-2)(x+2) \)[/tex].
### Part B: Non-equivalent Factored Forms
All the provided equations were factorable using the difference of squares method. There are no binomials in part A that did not have an equivalent factored form.
### Part C: Products using Properties of Complex Numbers
The products can be derived by simply expanding the factored forms back:
1. Product of [tex]\( (x - 6)(x + 6) \)[/tex]:
[tex]\[ (x - 6)(x + 6) = x^2 - 36 \][/tex]
2. Product of [tex]\( (3x - 1)(3x + 1) \)[/tex]:
[tex]\[ (3x - 1)(3x + 1) = 9x^2 - 1 \][/tex]
3. Product of [tex]\( 4(x - 2)(x + 2) \)[/tex]:
[tex]\[ 4(x - 2)(x + 2) = 4(x^2 - 4) = 4x^2 - 16 \][/tex]
Thus, the products of each expression, reaffirming the given factored forms, are the original expressions:
- [tex]\( (x-6)(x+6) = x^2 - 36 \)[/tex]
- [tex]\( (3x-1)(3x+1) = 9x^2 - 1 \)[/tex]
- [tex]\( 4(x-2)(x+2) = 4x^2 - 16 \)[/tex]
These steps confirm the accuracy and correctness of the original information, ensuring that the factored forms are appropriate and that all of the provided binomials are factorable.
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.